Euro-Par 2008 Workshops - Parallel Processing VHPC 2008, UNICORE 2008, HPPC 2008, SGS 2008, PROPER 2008, ROIA 2008, and DPA 2008, Las Palmas de Gran Canaria, Spain, August 25-26, 2008, Revised Selected Papers - César, Eduardo; Alexander, Michael; Streit, Achim; Traff, Jesper Larsson; Cérin, Christophe; Knüpfer, Andreas; Kranzlmüller, Dieter; Jha, Shantenu (Theoretical Computer Science and General Issues,, 2009)
This book constitutes the thoroughly refereed joint post-workshop proceedings of seven international events, held in Las Palma de Gran Canaria, Spain, in August 2008 within the scope of Euro-Par 2008, the 14th International Conference on Parallel Computing. The 43 papers presented together with 7 keynote lectures were carefully reviewed and selected during two rounds of reviewing and improvement from numerous presentations at the following workshops: the 3rd Workshop on Virtualization in High-Performance Cluster and Grid Computing (VHPC 2008), the UNICORE Summit 2008, the International Workshop on Highly Parallel Processing on a Chip (HPPC 2008), the Workshop on Secure, Trusted, Manageable and Controllable Grid Services (SGS 2008), the Workshop on Productivity and Performance (PROPER 2008), the Workshop on Real-Time Online Interactive Applications on the Grid (ROIA 2008), and the Workshop on Abstractions for Distributed Systems (DPA 2008).